2019
DOI: 10.1111/bjh.16232
|View full text |Cite
|
Sign up to set email alerts
|

No excess long‐term mortality in stage I‐IIA Hodgkin lymphoma patients treated with ABVD and limited field radiotherapy

Abstract: Summary When treating limited stage classical Hodgkin lymphoma (cHL), balancing treatment efficacy and toxicity is important. Toxicities after extended‐field radiotherapy are well documented. Investigators have aimed at reducing toxicity without compromising efficacy, mainly by using combined modality treatment (CMT), i.e. chemotherapy and limited‐field radiotherapy. In some clinical trials, radiotherapy has been omitted. We evaluated 364 patients with stage I‐IIA cHL treated between 1999 and 2005. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…OS rates exceeding 95% at 5 years [12][13][14]. In addition, a population-based study in Sweden and Norway also reported that there was no long-term excess mortality for limited-stage, favorable cHL patients diagnosed between 1999 and 2005 [27]. For patients with advanced-stage disease who were treated with ABVD or (escalated) BEA-COPP, 5-year OS rates approximate 90% [9,10] treatment-related sequelae associated with more intensive chemotherapeutic regimens, such as (escalated) BEACOPP [9,10].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…OS rates exceeding 95% at 5 years [12][13][14]. In addition, a population-based study in Sweden and Norway also reported that there was no long-term excess mortality for limited-stage, favorable cHL patients diagnosed between 1999 and 2005 [27]. For patients with advanced-stage disease who were treated with ABVD or (escalated) BEA-COPP, 5-year OS rates approximate 90% [9,10] treatment-related sequelae associated with more intensive chemotherapeutic regimens, such as (escalated) BEACOPP [9,10].…”
Section: Discussionmentioning
confidence: 96%
“…In this regard, a population-based cancer registry is a useful instrument to investigate how pivotal findings of clinical trials are implemented in routine clinical practice and affect outcomes among the general patient population. At present, large population-based studies in cHL including patients managed in contemporary clinical practice are scarce and mostly lack comprehensive information on patient characteristics and therapy or report OS rates that do not account for the expected survival from the general population [21][22][23][24][25][26][27]. Therefore, it remains mostly unknown how contemporary advances in cHL management have impacted survival at the population-level.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment regimens used were in accordance with Swedish national guidelines (supplemental Table 1). 33,34 Most patients, .80%, were treated primarily with doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD; 60%) or bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone (BEACOPP; 23%). Patients with stages I-IIA and selected patients with advanced disease ($IIB) received consolidating radiotherapy.…”
Section: Patient Characteristics and Treatmentmentioning
confidence: 99%
“…2,59 Most patients in our study were treated with what are still considered to be contemporary first-line therapies, for example, ABVD and BEACOPP. 34,59 Translational relevance and mechanism of action IL-6 cytokine downstream signaling pathways include mainly JAK/STAT3, phosphatidylinositol-3 kinase (PI3K)/protein kinase B (Akt), and Ras-MAPK. 1,7,60 These pathways induce upregulation of several genes that promote tumor progression 1,7,60 and chemotherapy resistance.…”
Section: Serum Il-6mentioning
confidence: 99%
“…15,16 In several large retrospective studies, survivors of HL who received RT experienced a significantly higher incidence of secondary malignancies than those who were treated with chemotherapy alone. 15,[17][18][19] It is expected that more modern RT techniques such as involved-site or node RT will reduce toxicity, 20 but the long-term effects of these newer RT techniques are still largely unknown. 21 In addition, both RT and anthracycline exposure have been associated with increased risk of cardiovascular complications, including congestive heart failure and coronary artery disease, in a dosedependent manner even at lower doses.…”
Section: Years From Diagnosismentioning
confidence: 99%